Correlation Analysis of Bacterial Community Structure and Biogenic Amines in Sufu - Weiya WANG; Yuting LIU; Hankun WAN; Yu LUO; Zhichao LIN; Jie LIU; Jinlin LI (Shipin gongye ke-ji, 2022)
In order to investigate the correlation of bacterial community structure and biogenic amines in sufu, Illumina Miseq high-throughput sequencing was used to analyze the bacterial community structure of sufu with different biogenic amines content and relevant environmental factors were determined. The results showed that Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes were the absolute dominant phyla and the relative abundance of the four phyla were more than 91% in sufu samples. Bacillus, Weissella, Tetragenococcus, and Pseudomonas were the main dominant genera in sufu. The main different genera between high and low biogenic amines content groups were Bacillus, Weissella, Pseudomonas and Lysinibacillus. Correlation analysis showed that biogenic amines and total acid were the main factors affecting bacterial community composition (P<0.05). The content of biogenic amines was mainly related to environmental factors such as amino acid nitrogen and pH. The content of amino acid nitrogen in sufu samples ranged from 0.62 to 0.86 g/100 g, and pH ranged from 5.62 to 6.37. Weissella, Bacillus and Lysinibacillus had a significant positive correlation with biogenic amines. Acinetobacter, Comamonas and Tetragenococcus had negtive correlation with biogenic amines. The research would elucidate the relationship between microbial community structure of sufu and biogenic amines, and provide a theoretical basis for understanding the formation mechanism of biogenic amines, effectively controlling biogenic amines and optimizing the production process of sufu.